John Donne's performances sermons, poems, letters and devotions - Fetzer, Margret; ebrary, Inc. (Manchester ; New York : Manchester University Press, 2010)
This is a comparative reading of Donne's poetry and prose, which eschews questions of personal or religious sincerity in order to recreate an image of John Donne as a man of many performances.
Introduction : beginning Donne -- Pulpit performances : sermons -- Promethean and protean performances : worldly poems -- Passionate performances : poems erotic and divine -- Patronage performances : letters -- (Inter)personal performances : devotions -- Conclusion : being Don(n)e -- Bibliography -- Index.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Donne, John, -- 1572-1631 -- Criticism and interpretation; Donne, John, -- 1572-1631.; Church of England. -- England -- Clergy; Poets, English -- Early modern, 1500-1700 -- Correspondence; Sermons, English -- 17th century -- History and criticism; Electronic books